2008
DOI: 10.1158/1535-7163.mct-07-2010
|View full text |Cite
|
Sign up to set email alerts
|

Potent synergy of dual antitumor peptides for growth suppression of human glioblastoma cell lines

Abstract: Molecular targeting agents have become formidable anticancer weapons, which show much promise against the refractory tumors. Functional peptides are among the more desirable of these nanobio-tools. Intracellular delivery of multiple functional peptides forms a basis for potent, non-invasive mode of delivery, providing distinctive therapeutic advantages. Here, we examine growth suppression efficiency of human glioblastomas by dualpeptide targeting.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 36 publications
1
32
0
Order By: Relevance
“…In total 10,000 cells were examined in each sample (FACScan, Becton Dickinson, USA). Cell cycle analysis was also performed by FACScan, using propidium iodide staining 20,21 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total 10,000 cells were examined in each sample (FACScan, Becton Dickinson, USA). Cell cycle analysis was also performed by FACScan, using propidium iodide staining 20,21 .…”
Section: Methodsmentioning
confidence: 99%
“…S4a). Antitumour peptides were designed by fusing CPP44 or CPP2, as cellpenetrating domains, to the minimal inhibitory sequence of p16 (p16MIS) that has been reported to restore lost p16 function via GPG sequence [19][20][21] (Fig. 4b).…”
Section: Isolation Of Tumour Lineage-homing Cppsmentioning
confidence: 99%
“…this transporter, wr-T, consisted of tryptophan-rich domains (serving as a cargo to attach functional peptides) fused with nine D-arginines serving as a PTD. They reported that the wr-T system provided higher delivery efficiency than Pep-1 (whose delivery efficiency is already reported) and achieved an antitumor effect by delivering antitumor peptides to leukemia, lymphoma and glioma cells (21)(22)(23). In the present study, we delivered antitumor peptides to renal cell carcinoma cell lines using a similar system, and evaluated their antitumor effect.…”
Section: Introductionmentioning
confidence: 71%
“…peptide purity was >95%. the amino acid sequence of the Wr-t transporter is: KetWWetWWteWWteWsQ GPGrrrrrrrrr (r, D-enantiomer arginine) (21,22). For the synthesis of p16 MIs, the 10 sequential amino acid residue sequence 'FlDTlVVlHR', identified as the mIs of p16 by Fahraeus et al (24), was defined as the functional core of the peptide, which is insoluble, as is the entire p16 molecule (mIs hydrophobicity, 69.2%).…”
Section: Cellsmentioning
confidence: 99%
See 1 more Smart Citation